2004
DOI: 10.1007/s00394-004-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of the potential side effects of long–term creatine supplementation in team sport athletes

Abstract: Our data shows that low-dose supplementation with creatine monohydrate did not produce laboratory abnormalities for the majority of the parameters tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
2
17
0
2
Order By: Relevance
“…Few longitudinal studies exist on the long-term effects of creatine supplementation. Schröder, Terrados, and Tramullas (2005) examined the effects of three years of daily creatine supplementation (5g/day) on professional Spanish basketball players Sixteen blood parameters were measured 5 times each year. Only creatine kinase was elevated above normal at each measurement point.…”
Section: Ergogenic Aids: Creatinementioning
confidence: 99%
“…Few longitudinal studies exist on the long-term effects of creatine supplementation. Schröder, Terrados, and Tramullas (2005) examined the effects of three years of daily creatine supplementation (5g/day) on professional Spanish basketball players Sixteen blood parameters were measured 5 times each year. Only creatine kinase was elevated above normal at each measurement point.…”
Section: Ergogenic Aids: Creatinementioning
confidence: 99%
“…Although they may refl ect muscle injury, they may be the lab equivalent of " that workout kicked my butt. " The literature available on the safety of creatine monohydrate supplementation does not support this hypothesis because the safety trials demonstrated normal liver and muscle enzymes ( 14 ). This patient's enzyme elevations, although not life-threatening, should be taken seriously.…”
Section: What Is the Most Likely Diagnosis?mentioning
confidence: 78%
“…The body of literature lacks supportive evidence for a causal relationship between supplement use and renal failure or arrhythmias, but the case reports suggest an association, while large amounts of literature convey marginal, if any benefi t from their use (4,6,10,14 ). The current body of literature, including the case reports and safety trials cited, suggests that these supplements have a neutral to poor cost-tobenefi t ratio, and are probably not safe for the general, unmonitored, aviation population.…”
Section: What Is the Most Likely Diagnosis?mentioning
confidence: 79%
“…Autores têm demonstrado um aumento por volta de 1 a 2 kg em 5 a 8 dias de suplementação 12 . Entretanto, muitos estudos têm relatado efeitos como desconfortos gastrintestinais, cãibras, desidratação, diarréias e vô-mitos principalmente em atletas 1,12,54 .…”
Section: -Efeitos Adversos Da Suplementa-ção Com Creatinaunclassified
“…Autores têm demonstrado que a suplementação com essa substância não afeta a função renal em animais com falência renal crônica 55 em atletas 54 e em estudos clínicos com pacientes em hemodiálise 20 . Wyss e Schulze 2 afirmam que são necessários estudos sistemáticos, melhor controlados e com métodos mais sensíveis para mensurar a função glomerular para comprovar os possíveis efeitos deletéri-os da ingestão de creatina sobre a função renal.…”
Section: -Efeitos Adversos Da Suplementa-ção Com Creatinaunclassified